1993
DOI: 10.2172/10185226
|View full text |Cite
|
Sign up to set email alerts
|

Hydrothermal processing of Hanford tank waste. Organic destruction technology development task annual report -- FY 1993

Abstract: This report was .prepared as an account of work sponsored by an agency of the United States Government. Neither the United States Government nor any agency thereof, nor any of their employees, make any warranty, express or implied, or assumes any legal liability or responsibility for the accuracy, completeness, or usefulness of any information, apparatus, product, or process disclosed, or represents that its use would not infringe privately owned rights. Reference herein to any specific commercial product, pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1995
1995
1996
1996

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…For an activation energy of 25 kcal/mole, approximately that reported for gas generation and related reactions (Delegard 1980;Ashby et al 1993;Meisel et al 1993;Orth et al 1993;Schmidt et al 1993Schmidt et al , 1994), a one-degree difference in temperature from 90°C would yield a 10% change in rate, a two-degree difference would yield a 20% change in rate, and a five-degree difference would yield a 60% change. The l-L reaction vessels were independently temperaturecontrolled and monitored throughout the tests to within f0.5"C, leading to a 5% error because of changes in thermal reaction rates and assuming a 25 kcal/mole activation energy.…”
Section: Experimental Methods For Gas Measurements and Sample Irradiamentioning
confidence: 77%
“…For an activation energy of 25 kcal/mole, approximately that reported for gas generation and related reactions (Delegard 1980;Ashby et al 1993;Meisel et al 1993;Orth et al 1993;Schmidt et al 1993Schmidt et al , 1994), a one-degree difference in temperature from 90°C would yield a 10% change in rate, a two-degree difference would yield a 20% change in rate, and a five-degree difference would yield a 60% change. The l-L reaction vessels were independently temperaturecontrolled and monitored throughout the tests to within f0.5"C, leading to a 5% error because of changes in thermal reaction rates and assuming a 25 kcal/mole activation energy.…”
Section: Experimental Methods For Gas Measurements and Sample Irradiamentioning
confidence: 77%
“…Successful oxidation of organic complexants in these thermal studies was anticipated from the observed behavior of wastes in Tank 241-SY-101. Orth et al (1993) heated simulated Tank 241-SY-101 waste containing various organic complexants at 200 "C for various times. He observed rapid oxidation of HEDTA and glycolate at 200 "C. Orth (1993) also found that at 200 "C EDTA decomposed at a reasonable rate but that NTA did not.…”
Section: Thermal Oxidationmentioning
confidence: 99%
“…Orth et al (1993) heated simulated Tank 241-SY-101 waste containing various organic complexants at 200 "C for various times. He observed rapid oxidation of HEDTA and glycolate at 200 "C. Orth (1993) also found that at 200 "C EDTA decomposed at a reasonable rate but that NTA did not. A temperature of 250 "C was required before NTA was oxidized at an appreciable rate.…”
Section: Thermal Oxidationmentioning
confidence: 99%